Пошаговое объяснение:
5 . A + B = 7 + 4y² + ( 2y - 1 )( 3 + y ) - 6y² = 7 + 4y² + 5y + 2y² - 3 - 6y² = 5y + 4 ;
5y + 4 = 8,4 ;
5y = 8,4 - 4 ;
5y = 4,4 ;
y = 4,4 : 5 ;
y = 0,88 . В - дь : А ) 0,88 .
6 . 1,3x * 6x + 9x * 1 5/9 - 78 * 0,1x² - 2,5x = 11,5x ;
11,5x = 48,3 ;
x = 48,3 : 11,5 ;
x = 4,2 . В - дь : х = 4,2 .
Пошаговое объяснение:
(7 + 4у²) + (2у-1)(3+у) - 6у² = 8,4
(7 + 4у²) + (6у + 2у² - 3 - у) - 6у² = 8,4
(7 + 4у²) + (5у + 2у² - 3) - 6у² = 8,4
7 + 4у² + 5у + 2у² - 3 - 6у² = 8,4
5у + 4 = 8,4
5у = 8,4 - 4
5у = 4,4
у = 4,4 : 5
у = 0,88
1,3х * 6х + 9х * 1. 5/9 - 78 * 0,1х² - 2,5х = 48,3
7,8х² + 126/9х - 7,8х² - 2,5х = 48,3
126/9х - 2,5х = 48,3
14х - 2,5х = 48,3
11,5х = 48,3
х = 48,3 : 11,5
х = 4,2